In defiance of time antiquarian writing in early modern England - Vine, Angus Edmund (Oxford : Oxford University Press, 2010)
'In Defiance of Time' contends that the antiquarian project integral to early modern literary & intellectual culture depended on the antiquaries' capacity to restore - in their imagination at least - the fragments of the past. It offers readings of important authors such as Leland, Stow, Spenser Camden, Drayton, & Selden.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Humanism in literature; History in literature; National characteristics, English, in literature